Sistem Pendukung Keputusan Seleksi Dosen Non Komputer Terbaik Menerapkan Metode SAW - Ilman Alfansyah; Jenberta Sibagariang; Rizkah Fadillah; Dwika Assarani (Journal of Decision Support System Research, 2023)
The role of lecturers at a university is one of the most influential parts on the quality of the resulting female students, one of which is a non-computer lecturer. At Budi Darma University there are many non-computer lecturers. So it is necessary to make an award to support the spirit of competition in terms of lecturer quality and will be chosen as the best lecturer. Giving the award is one way to foster positive competitiveness among non-computer lecturers on the level of competence of lecturers in the campus environment in order to produce non-computer lecturers with the best quality. Decision Support System is one of the alternatives in determining a decision, so this research aims to facilitate Higher Education Institutions (Foundations) in choosing the best non-computer lecturers who will get awards later. In building a decision support system, of course, by applying methods in data processing so that it will produce a decision value as expected. The method used to process non-computer lecturer data to produce the best non-computer lecturer data is the Simple Additive Weighting (SAW) method. The results of this research are using the SAW method, the best alternative is A4 for Lecturer D with a value of 0.485